Markers of redox status in patients with nonalcoholic fatty liver disease - Erceg, Sanja; Tomašević, Ratko; Ninić, Ana; Pavlović, Aleksandar; Guzonjić, Azra; Vujčić, Sanja; Mamić, Milica; Mitrović, Bojan; Gluvić, Zoran; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, present in up to 30% of the adult population worldwide. Triglycerides accumulation in hepatocytes (steatosis) represents the root cause of NAFLD and is associated with oxidative stress, which could further lead to fibrosis and cell death of hepatocytes. The aim of this research was to identify redox status markers for predicting the risk of developing steatosis. 158 participants were included. Steatosis was confirmed by ultrasound in 101 subjects, while the remaining 57 were in the control group. The following markers of redox status were determined in serum and plasma samples of all subjects: superoxide dismutase 1 (SOD1), paraoxonase (PON1), malondialdehyde (MDA) and superoxide anion (O2.-). For this purpose, spectrophotometric methods and enzyme immunosorbent assays were used. SOD1 was statistically significantly higher (P<0.001), while O2.- was significantly lower in the patient group (P<0.001). SOD1 was significantly negatively correlated with O2.- (ρ= -0.494, P<0.001) and MDA (ρ= -0.242, P=0.002). Univariate binary logistic regression analysis showed a positive association between SOD1 and the presence of steatosis (OR=1.018, 95% CI 1.005-1.031; P=0.005), as well as a negative association between O2.- and the presence of steatosis (OR=0.959, 95% CI 0.941-0.978; P<0.001). Multivariate analysis singled out SOD1 (OR=1.024, 95% CI 1.006-1.041; P=0.007) and O2.- (OR=0.965, 95% CI 0.942-0.989; P=0.004) as independent predictors for the presence of steatosis in our subjects. The redox status parameters, SOD1 and O2, respectively, showed a positive and negative prediction of the presence of statosis in our subjects.